2016
DOI: 10.1371/journal.pone.0154850
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Precision Medicine Research with African Americans

Abstract: ImportancePrecision medicine is an approach to detecting, treating, and managing disease that is based on individual variation in genetic, environmental, and lifestyle factors. Precision medicine is expected to reduce health disparities, but this will be possible only if studies have adequate representation of racial minorities.ObjectiveIt is critical to anticipate the rates at which individuals from diverse populations are likely to participate in precision medicine studies as research initiatives are being d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 23 publications
2
73
0
Order By: Relevance
“…Three studies reported consent rates lower than 50% in their sample (Halbert et al, ; Hensley Alford et al, ; Jazwinski et al, ). Halbert et al reported a 31% intention to participate rate among African American participants ( n = 150) for a hypothetical government‐sponsored study with open data sharing and no option for participants to receive individual results (Halbert et al, ). Jazwinski et al and Hensley Alford et al reported lower participation rates among a subset of their participants in their studies measuring actual consent; namely 41% of Asian American participants ( n = 51; Jazwinski et al, ) and 30% of African American participants ( n = 3,740; Hensley Alford et al, ) were willing to consent for genetic testing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies reported consent rates lower than 50% in their sample (Halbert et al, ; Hensley Alford et al, ; Jazwinski et al, ). Halbert et al reported a 31% intention to participate rate among African American participants ( n = 150) for a hypothetical government‐sponsored study with open data sharing and no option for participants to receive individual results (Halbert et al, ). Jazwinski et al and Hensley Alford et al reported lower participation rates among a subset of their participants in their studies measuring actual consent; namely 41% of Asian American participants ( n = 51; Jazwinski et al, ) and 30% of African American participants ( n = 3,740; Hensley Alford et al, ) were willing to consent for genetic testing.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of participants believed genetic research produces beneficial outcomes to society and that there are personal benefits to individuals who participate in genetic research (Akinleye et al, 2011;Buseh et al, 2014Buseh et al, , 2012Frazier et al, 2006;Freedman et al, 2013;Halbert, Gandy, Collier, & Shaker, 2006;Halbert, McDonald, Vadaparampil, Rice, & Jefferson, 2016;Hooper et al, 2013;Hull et al, 2008;Jenkins et al, 2011;Kinney et al, 2006;Lakes et al, 2013;Murphy & Thompson, 2009;Pettey et al, 2015;Rew et al, 2010;Sanderson et al, 2017). The most often cited reasons for participating in genetic testing and research were to learn more information, to contribute to the development of medical treatments and prevention of disease, and to positively impact future generations.…”
Section: Subtheme A: Motivations For Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Americans perceived individual, family, and community benefits of participating in genetic research for cancer; however, they also reported reasons for being hesitant to participate, including distrust of researchers and concerns about exploitation and mishandling of genetic information (McDonald et al, 2014). In a national survey of African Americans, distrust in research was the only significant barrier or facilitator to participating in a hypothetical genetic study for cancer after controlling for education, employment, and healthcare access (Halbert, McDonald, Vadaparampil, Rice, & Jefferson, 2016;McDonald et al, 2014McDonald et al, , 2012.While the studies in this review did not focus on research participation, one study found that Blacks had more concerns about genes being used without consent and genetic information being shared without consent. Lower participation of racial and ethnic minority groups in genetic studies will delay groupspecific precision medicine developments.…”
Section: Collinsmentioning
confidence: 99%
“…Our analysis, however, found that African American/Blacks in our study population did not consider trust to be more important than Whites when deciding to get a genetic test. This result was somewhat surprising given existing literature highlighting the importance of trust in genetic testing and the lower trust in healthcare providers held by African American/Blacks relative to Whites (Halbert et al ). Regardless, researchers and practitioners should continue to explore the cultural and historical background patients may bring to precision medicine initiatives and design methods to support these varying values.…”
Section: Discussionmentioning
confidence: 73%